A highly sensitive and selective spectrophotometric method for the determination of vanadium at nanotrace levels in some environmental, biological, soil, food, and pharmaceutical samples using salicylaldehyde-benzoylhydrazone - Abrarin, Shaifa; Ahmed, Mohammed Jamaluddin (European Journal of Chemistry, 2020)
A very simple, non-extractive and new spectrophotometric method for the swift determination of trace amount of vanadium using salicylaldehyde-benzoylhydrazone (Sal-BH) has been developed. Sal-BH undergoes a reaction in a slightly acidic solution (0.0016-0.0032 M H2S04) with vanadium to give a light greenish-yellow chelate, which has an absorption maximum at 392 nm. The reaction is instantaneous and absorbance remains stable for over 24 hrs. The average molar absorption co-efficient and Sandell’s sensitivity were found to be 2.5039×105 L/mol.cm and 1.0 ng/cm2 V, respectively. Beer’s law was obeyed for 0.001-30 mg/L of V, providing a detection limit of 0.1 µg/L of V and RSD 0-2 %. The stoichiometric composition of the chelate is 1:1 (V:Sal-BH). Interference study shows that a large excess of over 60 cations, anions, and some common complexing agents (such as chloride, azide, tartrate, EDTA and SCN‑, etc.) satisfy the tolerance limit. The developed method was successfully used in the determination of vanadium in several standard reference materials as well as in some environmental waters, biological fluids, soil, food and pharmaceutical samples and solutions containing both vanadium (IV) and vanadium (V). The results of the proposed method for assessing biological, food and vegetable samples were comparable with ICP-OES and AAS were found to be in excellent agreement. The method has high precision and accuracy (s = ±0.01 for 0.5 mg/L).